SUBTITUSI SAMPAH ORGANIK DAN TANAH MEDITERAN MENJADI SEMEN ALTERNATIF SELAIN SEMEN PORTLAND - Muhammad Syarif; Victor Sampebulu; Muh. Wihardi Tjaronge; Nasruddin Junus (Jurnal Teknosains, 2018)
The results of this study aims to save the environment, through the discovery of new alternative materials by recycling organic waste, household waste, coal waste (fly ash and bottom ash), and substitution of mediteran land and clay into organic cement that is alternative cement in addition portland cement. Test results of organic cement chemical compound using laboratory testing method refers to ASTM C-114 and SNI 15-2049-2004. An indication of resembling a portland cement chemical compound is CaO of 65.36%, SiO₂ 18.84%, AlOO₃ 6.33%, Fe₂O₃ 2.29%, SO₃ 3.64%, MgO 1.35%, C₃S 66 , 72%, C₂S 3.98%, C₃A 12.9%, and C4Af 6.97%. Test methods of physical properties include testing of baseline time and end time and normal consistency value to organic cement, this test refers to ASTM C 191-04 and C 191-08 and ASTM C 187-04. Fineness of organic cement grains that passed in the mesh 200 mesh as much as 56%, more subtle than portland cement is 52%. The solid weight of organic cement is 1200 kg/m3, lighter than portland cement which reaches 1250 kg/m3. The initial setting time for organic cement was 105 minutes, longer than portland cement at 90 minutes. For the organic cement final time at 225 minutes, it was above the end time of portland cement at 180 minutes.